A Modified Surgical Technique for the Reduction of Posterior Cruciate Ligament Avulsion Fragment during Cruciate-retaining Total Knee Arthroplasty - Yang-Yi Wang; Ming-Chou Ku; Yuan-Hsin Tsai (Formosan Journal of Musculoskeletal Disorders)
Background: With rising life expectancy, osteoarthritis, particularly impacting the knee, becomes more prevalent. Objectives: This study presents a modified technique for dealing with posterior cruciate ligament (PCL) injuries, a common complication of knee osteoarthritis, during cruciate-retaining total knee arthroplasty (CR-TKA). Materials and Methods: From 2020 to 2022, we conducted a retrospective search on 319 CR total knee replacement surgeries, focusing on patients meeting specific criteria. Five patients with PCL avulsion were identified and treated. The outcomes were tracked using postsurgical range of motion (ROM), pain levels, and Oxford knee scores. Follow-ups were conducted for patients absent from clinics for over 6 months postsurgery. Results: Out of these cases, five patients (average age 66.2 ± 10.3 years, 80% female) had PCL injuries and underwent a modified reduction technique for PCL repair. The average incidence rate of PCL injury in CR-TKA was found to be 1.6%, which aligns with previous studies. Their average knee ROM was from 0 to 125° ±5°, and they achieved near-perfect Oxford knee scores of 44 ± 1.6. These results affirm the positive impact of the applied repair technique on CR-TKA PCL injury cases. Conclusions: The study validates the positive impact of a modified PCL repair technique during CR-TKA on function and pain. This method is particularly useful for managing surgical PCL injuries in osteoporosis-prone patients, although additional research for further validation and comparison is required.